Pendampingan Badan Usaha Milik Desa (BUMDes) Alam Sentosa Desa Kurungan Nyawa - Rio Kurniawan; Ni Nengah Rizki Noventy; Ukhti Ciptawaty; Ambya Ambya; Heru Wahyudi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: This service activity for BUMDes Alam Sentosa, Kurungan Nyawa Village, aims to provide an overview of the development and management of BUMDes which functions as a driving force for the village economy. Method: Methods of instruction, guidance, and assessment are employed in this operation. Results: The findings of this program provide a process that is carried out by a person in managing activities carried out by individuals or groups. The system or management must be carried out to meet the targets to be achieved by the individual or group in a collaboration by optimizing existing resources. Conclusions: The service activity of mentoring BUMDes Alam Sentosa in Kurungan Nyawa Village went well and offered a stimulus in the form of motivation for BUMDes Alam Sentosa in carrying out its businesses, both those that were carried out and those that were not. The presence of a formal organization authorized by the Ministry of Villages is supposed to assist BUMDes Alam Sentosa's access to doing business and working with companies. Limitations: The limitation of this service is the implementation time. Contribution: This service can be useful for the BUMDes Alam Sentosa, rural communities, and the economy of the confinement village.